La comunicación y su influencia en la relación de pareja de los cónyuges del barrio Sauces norte y la intervención del trabajador social - Asanza Salazar, Joselyne Maritza (2019)
The present study is part of an investigation about the current reality in which the couples of spouses live and the types of communication that are present in the daily life. Based on this reality, communication is investigated and its influence on the couple's relationship between the spouses of the North Willows neighborhood and the intervention of the social worker, with the general objective of knowing the types of communication that influence the relationship of the Sauces neighborhood couples North of the city of Loja, for the elaboration of a social action plan .; as a specific objective to identify the type of communication used by the couples of the Sauces Norte community in the city of Loja; characterize the couple's relationship with the spouses of the Sauces Norte neighborhood of the city of Loja; and, finally, design a proposal for social action to improve communication in the couple's relationship of the spouses of the Sauces Norte community in the city of Loja. The present study had the participation of 15 spouses, the methodology used was based on the scientific, inductive, deductive, and qualitative methods, through the use of research techniques and instruments such as the observation form, focal group and interview that allowed to give compliance with the objectives set in the research process. The main findings obtained in the research, it is established that the dominant types in the relationship are the passive and aggressive which are present and are outstanding in the marital life themselves that bring different problems in the relationship, which is declining with the weather. Finally, it was considered pertinent to present a proposal for social action to help strengthen the type of assertive communication of the groups of spouses of the Sauces Norte community in the city of Loja. In the research process it is not only necessary to identify the existing problem, but also the solution alternatives that respond to this problem, that is why based on the results obtained in the research a social action proposal called "AMA WITH PASSION, COMMUNICATE WITH WISDOM "which aims to strengthen the type of assertive communication of the groups of spouses through activities that promote good assertive communication.